High-density lipoprotein metabolism and reverse cholesterol transport: strategies for raising HDL cholesterol - Katerina Tosheska Trajkovska; Sonja Topuzovska (Turkish Society of Cardiology, 2017)
A key to effective treatment of cardiovascular disease is to understand the body’s complex lipoprotein transport system. Reverse cholesterol transport (RCT) is the process of cholesterol movement from the extrahepatic tissues back to the liver. Lipoproteins containing apoA-I [highdensity lipoprotein (HDL)] are key mediators in RCT, whereas non-high-density lipoproteins (non-HDL, lipoproteins containing apoB) are involved in the lipid delivery pathway. HDL particles are heterogeneous; they differ in proportion of proteins and lipids, size, shape, and charge. HDL heterogeneity is the result of the activity of several factors that assemble and remodel HDL particles in plasma: ATP-binding cassette transporter A1 (ABCA1), lecithin cholesterol acyltransferase (LCAT), cholesteryl ester transfer protein (CETP), hepatic lipase (HL), phospholipid transfer protein (PLTP), endothelial lipase (EL), and scavenger receptor class B type I (SR-BI). The RCT pathway consists of the following steps: 1. Cholesterol efflux from peripheral tissues to plasma, 2. LCAT-mediated esterification of cholesterol and remodeling of HDL particles, 3. direct pathway of HDL cholesterol delivery to the liver, and 4. indirect pathway of HDL cholesterol delivery to the liver via CETP-mediated transfer There are several established strategies for raising HDL cholesterol in humans, such as lifestyle changes; use of drugs including fibrates, statins, and niacin; and new therapeutic approaches. The therapeutic approaches include CETP inhibition, peroxisome proliferator-activated receptor (PPAR) agonists, synthetic farnesoid X receptor agonists, and gene therapy. Results of clinical trials should be awaited before further clinical management of atherosclerotic cardiovascular disease.
Keywords: igh-density lipoprotein; LCAT; CETP; remodeling; reverse cholesterol transport